Everyday representations of tax avoidance, tax evasion, and tax flight: Do legal differences matter? - Erich Kirchler; Boris Maciejovsky; Friedrich Schneider (Humboldt University of Berlin, Interdisciplinary Research Project 373: Quantification and Simulation of Economic Processes, 2001)
From an economic point of view, legal considerations apart, tax avoidance, tax evasion and tax flight have similar effects, namely a reduction of revenue yields, and are based on the same desire to reduce the tax burden. Due to legal differences and moral concerns it is, however, likely that individuals perceive them as different and as unequally fair. Overall, 252 fiscal officers, business students, business lawyers, and entrepreneurs produced spontaneous associations to a scenario either describing tax avoidance, tax evasion, or tax flight, and evaluated them as positive, neutral or negative. The results indicate that everyday representations differ with respect to tax avoidance, tax evasion, and tax flight. Tax evasion was perceived rather negatively, tax flight neutrally, and tax avoidance positively. Although fiscal officers judged all forms of tax reduction least fair, all sub-samples found tax evasion less fair than tax avoidance or tax flight. With regard to knowledge of tax law and fairness perception, differential effects were found: Business lawyers and entrepreneurs judged tax avoidance the fairer the higher their knowledge was. Fiscal officers, on the other hand, found tax evasion especially unfair if their knowledge was high.
urn:nbn:de:kobv:11-10049881
Keywords: H26; K34; K42; 330; Tax Evasion; Everyday Representations; Tax Knowledge